1242 CO-MORBIDITY, FRAILTY AND EJECTION FRACTION IN OLDER HEART FAILURE INPATIENTS. (16th January 2023) - Shah, G; Nehikhare, I; Obiechina, N; Michael, A; Gill, A; Carey, P; Khan, R; Slavica, M; Khan, T; Rahman, S; Mushtaq, W; Brar, H; et al.
Abstract: Introduction: Co-morbidities and frailty are common in older heart failure patients. The aim of this study is to explore the relationship between co-morbidity, frailty and ejection fraction (EF) in older heart failure inpatients Methods: A cross-sectional, observational, retrospective analysis of consecutive patients aged 60 years and over who were admitted with heart failure in a UK hospital. Patients with incomplete data were excluded. The Carlson's comorbidity index (CCI) was used to compute comorbidity and the Rockwood Clinical Frailty Scale (CFS) was used to measure frailty. The EF was calculated as the midpoint of the ranges measured by echocardiography. IBM SPSS 28 software was used for statistical analysis. Descriptive statistics were used to measure baseline characteristics and Pearson's correlation coefficient and linear regression were used to calculate correlation. Results and discussion: 101 patients were analysed; 48 males and 53 females. Mean age was 81.2 years(SD 9.98). Mean CCI was 6.97(SD 1.63) and mean CFS was 5.09(SD 1.14). There was statistically significant positive correlation between CCI and CFS (r= 0.232; p= .01). There was statistically significant inverse correlation between CCI and EF (r= -.277; p=. 005). When taking into account the level of frailty the correlation between CCI and EF was much stronger in non-frail than in frail patients (r= -.612; p=. 035 and r= -.216; p= .047 respectively). There was no correlation between CFS and EF (r= .095; p=.26). This was not surprising as HFpEF is the most common type of HF in the elderly. HFpEF patients are more likely to have more comorbidities and to be more frail compared to HFrEF patients. Conclusion: There was a positive correlation between multi-morbidity and frailty in older inpatients admitted with heart failure. There was statistically significant inverse correlation between CCI and ejection fraction but there was no correlation between frailty and ejection.